An Intracerebral Hemorrhage Care Bundle Is Associated with Lower Case Fatality. Issue 4 (16th August 2019) - Parry‐Jones, Adrian R.; Sammut‐Powell, Camilla; Paroutoglou, Kyriaki; Birleson, Emily; Rowland, Joshua; Lee, Stephanie; Cecchini, Luca; Massyn, Mark; Emsley, Richard; Bray, Benjamin; Patel, Hiren
Abstract : Objective: Anticoagulation reversal, intensive blood pressure lowering, neurosurgery, and access to critical care might all be beneficial in acute intracerebral hemorrhage (ICH). We combined and implemented these as the "ABC" hyperacute care bundle and sought to determine whether the implementation was associated with lower case fatality. Methods: The ABC bundle was implemented from June 1, 2015 to May 31, 2016. Key process targets were set, and a registry captured consecutive patients. We compared 30‐day case fatality before, during, and after bundle implementation with multivariate logistic regression and used mediation analysis to determine which care process measures mediated any association. Difference‐in‐difference analysis compared 30‐day case fatality with 32, 295 patients with ICH from 214 other hospitals in England and Wales using Sentinel Stroke National Audit Programme data. Results: A total of 973 ICH patients were admitted in the study period. Compared to before implementation, the adjusted odds of death by 30 days were lower in the implementation period (odds ratio [OR] = 0.62, 95% confidence interval [CI] = 0.38–0.97, p = 0.03), and this was sustained after implementation (OR = 0.40, 95% CI = 0.24–0.61, p < 0.0001). Implementation of the bundle was associated with a 10.8 percentage point (95% CI = −17.9 to −3.7, p = 0.003) reduction in 30‐day case fatality in difference‐in‐difference analysis. The total effect of the care bundle was mediated by a reduction in do‐not‐resuscitate orders within 24 hours (52.8%) and increased admission to critical care (11.1%). Interpretation: Implementation of the ABC care bundle was significantly associated with lower 30‐day case fatality after ICH. ANN NEUROL 2019;86:495–503